Pancreatic Aquaporin-7: A Novel Target for Anti-diabetic Drugs? - Méndez-Giménez, Leire; Ezquerro, Silvia; da Silva, Inês V.; Soveral, Graça; Frühbeck, Gema; Rodríguez, Amaia (Frontiers in Chemistry, 2018)
Aquaporins comprise a family of 13 members of water channels (AQP0-12) that facilitate a rapid transport of water across cell membranes. In some cases, these pores are also permeated by small solutes, particularly glycerol, urea or nitric oxide, among other solutes. Several aquaporins have been identified in the pancreas, an exocrine and endocrine organ that plays an essential role in the onset of insulin resistance and type 2 diabetes. The exocrine pancreas, which accounts for 90% of the total pancreas, secretes daily large volumes of a near-isotonic fluid containing digestive enzymes into the duodenum. AQP1, AQP5 and AQP8 contribute to fluid secretion especially from ductal cells, whereas AQP12 allows the proper maturation and exocytosis of secretory granules in acinar cells of the exocrine pancreas. The endocrine pancreas (10% of the total pancreatic cells) is composed by the islets of Langerhans, which are distributed in ,, ,  and pancreatic polypeptide (PP) cells that secrete glucagon, insulin, somatostatin, ghrelin and PP, respectively. AQP7, an aquaglyceroporin permeated by water and glycerol, is expressed in pancreatic -cells and murine studies have confirmed its participation in insulin secretion, triacylglycerol synthesis and proliferation of these endocrine cells. In this regard, transgenic AQP7-knockout mice develop adult-onset obesity, hyperinsulinemia, increased intracellular triacylglycerol content and reduced -cell mass in Langerhans islets. Moreover, we have recently reported that AQP7 upregulation in β-cells after bariatric surgery, an effective weight loss surgical procedure, contributes, in part, to the improvement of pancreatic steatosis and insulin secretion by increasing intracellular glycerol in obese rats. Human studies remain scarce and controversial, with some rare cases of loss-of function variants of the AQP7 gene being associated with the onset of type 2 diabetes. The present Review is focused on the role of aquaporins in the physiology and pathophysiology of the pancreas, highlighting the role of pancreatic AQP7 as a novel player in the control of -cell function and a potential anti-diabetic-drug.